Understanding Depression Volume 2. Clinical Manifestations, Diagnosis and Treatment (Springer Singapore, 2018)
This book, in two volumes, focuses on contemporary issues and dilemmas in relation to depression. The aim is to equip readers with an up-to-date understanding of the clinical and neurobiological underpinnings of depression, the clinical manifestations, and the development of more effective treatments. This second volume is devoted specifically to clinical and management issues. Readers will find detailed information on a wide range of frequently encountered and more complicated clinical presentations, with examination of risk factors and links to other conditions. Diagnostic aspects, including progress toward biological classification and the role of neuroimaging, are explored. Current trends in therapy are examined at length, drawing on the latest evidence and covering not only antidepressant medications but also the roles of neurostimulation, combined pharmacotherapy and psychotherapy, mindfulness-based cognitive therapy, and complementary and alternative medicine. The companion volume is dedicated to the underlying biomedical and neurobiological basis of depression. Understanding Depression will be an excellent source of information for both researchers and practitioners in the field.